The Dilemma of Applying Authentic Assessment to Aqidah Akhlak Subjects - Saibatul Hamdi; Muslimah Muslimah (Nazhruna: Jurnal Pendidikan Islam, 2022)
The purpose of this study is to describe: (1) describe the implementation of the assessment carried out by Akidah Akhlak teachers; (2) identify the factors that cause the teacher's dilemma in carrying out authentic assessments on the subject of Akidah Akhlak. The approach used in this study is a descriptive qualitative approach. Data collection techniques using interviews, observation, and documentation. The data validation technique uses source and technique triangulation. While the data analysis technique uses the Miles and Huberman model. The results of this study indicate that: (1) the implementation of authentic assessment on Akidah Akhlak subjects at MA Sabilal Muhtadin has not been carried out optimally, it can be seen from teachers who only provide assessments on cognitive aspects through written tests, while psychomotor aspects have not been carried out. As for the affective aspect, the teacher carried out observations but did not use instruments. (2) The dilemma of teachers in carrying out authentic assessments is caused by three main factors, namely minimal resources, the dogma of the KTSP assessment that is still strong, and the busy factor coupled with the shortening of offline learning time during the pandemic. The implementation of the assessment should be supported by various parties by improving the quality of existing resources as an effort to improve Islamic Education Subject assessment in madrasas.